Tolerogenic Splenic IDO+ Dendritic Cells from the Mice Treated with Induced-Treg Cells Suppress Collagen-Induced Arthritis - Jie Yang; Yiming Yang; Huahua Fan; Hejian Zou (Journal of Immunology Research)
TGF-β-induced regulatory T cells (iTregs) retain Foxp3 expression and immune-suppressive activity in collagen-induced arthritis (CIA). However, the mechanisms whereby transferred iTregs suppress immune responses, particularly the interplay between iTregs and dendritic cells (DCs) in vivo, remain incompletely understood. In this study, we found that after treatment with iTregs, splenic CD11c+DCs, termed “DCiTreg,” expressed tolerogenic phenotypes, secreted high levels of IL-10, TGF-β, and IDO, and showed potent immunosuppressive activity in vitro. After reinfusion with DCiTreg, marked antiarthritic activity improved clinical scores and histological end-points were observed. The serological levels of inflammatory cytokines and anti-CII antibodies were low and TGF-β production was high in the DCiTreg-treated group. DCiTreg also induced new iTregs in vivo. Moreover, the inhibitory activity of DCiTreg on CIA was lost following pretreatment with the inhibitor of indoleamine 2,3-dioxygenase (IDO). Collectively, these findings suggest that transferred iTregs could induce tolerogenic characteristics in splenic DCs and these cells could effectively dampen CIA in an IDO-dependent manner. Thus, the potential therapeutic effects of iTregs in CIA are likely maintained through the generation of tolerogenic DCs in vivo.